Resistência de união entre cerâmica à base de dissilicato de lítio e cimentos resinosos : efeito do tratamento de superfície da cerâmica, do sistema de cimentação e da aplicação de adesivo - Moraes, Julia Rocha (2010)
The aim of this in vitro study was to evaluate the micro shear bond strength of three bonding systems to a lithia dissilicate-based ceramic after performing different surface treatment techniques and to evaluate the effect of adhesive application prior to a self-adhesive resin cement. Fifty four ceramic disks (IPS Empress 2, Ivoclar Vivadent) were divided in groups according to the surface treatments: no treatment (NT); 50μm alumina sandblasting (AL); 10% hydrofluoric acid etching for 20s (HF); AL + HF (ALHF); HF + 37% phosphoric acid cleaning for 40s (HFP) and AL + HFP (ALHFP). One conventional bonding system, Excite DSCVariolink II- Ivoclar Vivadent (EX/V2) and two self-adhesive bonding system , Single bond 2/ RelyX U100 3M ESPE (SB2/UC) and RelyX U100 without adhesive (UC) were tested for each surface treatment. After silanization and adhesive application, Tygon tubes of 0.8 mm diameter and 2mm height were filled with cement and pressed against the ceramic surface to fabricate the specimens (n=10), that were stored in 37º C distilled water for 24h and then subjected to shear tension at a crosshead speed of 1 mm/min until fracture. Scanning electron microscopy observation of fractured surfaces was performed to determinate the type of fracture. Kruskal-Wallis and Mann-Whitney tests showed statistically different bond strengths values between the treatments for both bonding systems (p< 0.05). For systems EX/V2 and UC, the values of the treatment NT was lower than AL, which was equal to ALHF, which was lower than HF, which was lower than HFP, which was equal to ALHFP. For system SB2/UC, the values of the treatment NT was lower than HF, which was equal to ALHF, which was lower than AL, which was lower than HFP, which was equal to ALHFP. Bond strength value of SB2/UC was lower than EX/V2 only with HF treatment, and EX/V2 was equal to SB2/UC for all other treatments. The bonding system SB2/UC had higher bond strength values than UC only for AL treatment. For all other treatments, the values of UC and SB2/UC did not differ. The adhesive type of fracture was predominant for NT treatment and the mix type of fracture occur more frequently on the other treatments than on NT. It was concluded that: (1) lithia dissilicate-based ceramic surface treatment with hydrofluoric acid etching followed by phosphoric acid cleaning was most effective to increase bond strength to the two resin cements tested; (2) bond strength difference between cements could only be seen with fluoric acid treatment alone, with the conventional resin cement having higher bond strength than self-adhesive resin cement; (3) Adhesive application before self-adhesive resin cement did not improve bond strength for all treatments tested, except for sandblasting